Stress profile among Fayoum University students - Eman Hanafy Mohamed Ebrahim; Abeer Abdou Barakat; Naglaa Abdelkhalek Elsherbeny; Nargis Albert Labib (Cairo : Eman Hanafy Mohamed Ebrahim, 2010)
The aim of this study was to assess the sources of stress among Fayoum University students symptoms of stress the stress the stress levels and the coping strategies they used to overcome these stresses the study also compared between medical and non medical students as well between the academic and clinical medical groups and between male and female students
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Community Medicine
Issued also as CD
Keywords: Coping; Stress; Students